(untitled) (Journal of Management and Educational Sciences, 2025)
This study aims to examine the effect of organizational culture on teachers’ professional learning according to teachers’ opinions. The study was conducted with a relational screening model. According to the research results; teachers’ professional learning and organizational culture perceptions were above average. Especially the high average of teachers’ professional learning shows the importance that teachers give to their professions. In the examination according to gender; teachers’ professional learning and organizational culture perceptions do not change according to male or female. In the examination according to age groups; teachers’ professional learning and organizational culture perceptions do not change according to age groups. In the examination according to years of service; teachers’ professional learning and organizational culture perceptions do not change according to years of service groups. In the examination according to their participation in professional development courses; the perception of teachers who participate in professional development courses every year is higher than those who do not participate in any courses. On the other hand, organizational culture perceptions do not change according to their participation in professional development courses. Finally, there is a moderate, significant and positive relationship between teachers’ professional learning scores and organizational culture scores. Again, teachers’ organizational culture perceptions significantly predict their professional learning perceptions. Accordingly, a 100-unit increase in the organizational culture dimension of the participants increases professional learning behavior by 32.9%.